2019
DOI: 10.3389/fcimb.2018.00452
|View full text |Cite
|
Sign up to set email alerts
|

The XRE Family Transcriptional Regulator SrtR in Streptococcus suis Is Involved in Oxidant Tolerance and Virulence

Abstract: Streptococcus suis is a zoonotic pathogen that harbors anti-oxidative stress genes, which have been reported to be associated with virulence. Serial passage has been widely used to obtain phenotypic variant strains to investigate the functions of important genes. In the present study, S. suis serotype 9 strain DN13 was serially passaged in mice 30 times. The virulence of a single colony from passage 10 (SS9-P10) was found to increase by at least 140-fold as indicated by LD50 values, and the increased virulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 71 publications
2
35
0
2
Order By: Relevance
“…1cj). The complementary strain Δncgl2679 + exhibited a growth rate equivalent to that of the wild-type strain under various stresses, consistent with a previous evaluation of XREs under stress [19]. These results indicated that NCgl2679 is involved in the resistance of C. glutamicum to various stresses.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…1cj). The complementary strain Δncgl2679 + exhibited a growth rate equivalent to that of the wild-type strain under various stresses, consistent with a previous evaluation of XREs under stress [19]. These results indicated that NCgl2679 is involved in the resistance of C. glutamicum to various stresses.…”
Section: Resultssupporting
confidence: 89%
“…Thus, our results provided, for the first time, insight into a new regulatory mechanism adopted by an XRE protein in which DNA-binding ability is regulated by the oxidation of a cysteine residue in the MsrR protein in response to oxidants but not directly bound ligands, such as antibiotics, heavy metals, and alkylating agents. Our data further confirmed the results of Hu et al showing a member of the XRE family of transcriptional regulators responsible for oxidant tolerance in bacteria [19], facilitating understanding of antioxidant mechanisms in bacteria and providing initial insight into the molecular mechanisms of XREs involved in oxidative stress tolerance. In addition, MsrR is found to be widely distributed in several species of the genera Corynebacterium, such as C. crudilactis, C. efficiens, C. callunae, C. epidermidicanis, and C. minutissimum.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations